Factors Affecting the Competencies of Quantity Surveyors in Tendering for Construction Projects in Cambodia - Heng, Chakreya; Aksorn, Preenithi (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
Quantity surveyors are involved in every stage of construction project, particularly in developing countries such as Cambodia's construction industry, where they play a crucial role in managing costs from the initiation as in tendering phase to the closure of the project. Despite their importance, issues such as a high risk of failure during tendering, poor cost management and cost overruns are still prevalent. This is largely attribute to a lack of competency among quantity surveyors who rely on traditional skills, hindering their ability to compete in an emerging market. To address these issues, especially those related to tendering, this research aimed to determine the factors affecting quantity surveyor competencies in the tendering procedure. Data collections were gathered through online surveys from 416 civil engineers with varying levels of experience and analyzed through exploratory factor analysis. Results showed that six group factors influencing quantity surveyor’s competencies in tendering procedure were identified: 1. technical factors in cost estimating and information technology (17 items); 2. technical factors in construction methodology and site analysis group (8 items); 3. managerial factors impacting project success (contract, schedule, stakeholders, cost, and manpower management planning) (18 items); 4 managerial factors in soft skill (9 items); 5 attitude (4 items); 6. external factors in education and training, experience and market. The finding helps Cambodians civil engineers who work as quantity surveyor to understand the significant influencing factors to be strengthen their competencies in practicing in tendering construction project